Analysis of Six Orthodontic Journals in Science Citation Index and Science Citation Index Expanded: A Bibliometric Analysis - Fundagül Bilgiç; Eyüp Burak Küçük; Özlem Akıncı Sözer; Yazgı Ay; Abdullah Kaya; Murat Kaptaç (Galenos Yayinevi, 2018)
Objective:To analyze the article type, origin, main affiliation, number of publications, authors, and affiliations of six orthodontic journals during two intervals of 5 years each (2006-2010 and 2011-2015).Methods:In total, 4879 articles examined in this study were screened online at the individual journal's website. The types of articles and their authorship characteristics in the six orthodontic journals [three journals indexed by Science Citation Index (SCI) and the others indexed by Science Citation Index Expanded (SCIE)] were recorded. Parameters were tested using the Pearson chi-square for independence at a 0.05 level of significance.Results:Among all the article types, research articles were the most published in the orthodontic journals indexed by SCI and SCIE in the first (2006-2010; 88.1% and 77.6%, respectively) and second periods (2011-2015; 84.4% and 74.6%, respectively). In the first and second intervals, the European Union was the most common origin among articles accepted by the journals listed in SCI (30.1% and 29.2% respectively), whereas Asia/Oceania was the common origin among articles accepted by the journals listed in SCIE (44.1% and 43.4%, respectively).Conclusion:The articles published in the orthodontics journals listed under SCI and SCIE for 2006-2010 and 2011-2015 were significantly different in terms of numbers and characteristics.